Enchentes no Rio de Janeiro: efeitos da urbanização no Rio Grande (arroio fundo) - Jacarepaguá - Ferreira, Francisco Pontes de Miranda; Cunha, Sandra Baptista da (Anuário do Instituto de Geociências, 1996)
Human participation as an agent in the modification of hydrologie conditions in urban areas has a direct relation with the processes of erosion, deposition and transport of material in river channels. Engineering work as deepening and rectification of the channel and modification in the surrounding vegetation, cause important impacts. The urban development of Jacarepagua and Barra da Tijuca districts has been causing alterations in the Grande river drainage system. In February of 1996, the flooding of the Grande river provoked more than 30 deaths, leaving hundreds of people homeless.